Role of Toll-like receptors, NOD-like receptors and RIG-I-like receptors in endothelial cells and systemic infections - Opitz, Bastian; Eitel, Julia; Meixenberger, Karolin; Suttorp, Norbert (Thrombosis and Haemostasis, 2009)
Bacteraemia and viraemia are characterised by pathogens entering the bloodstream. Endothelial cells are among the first cells coming into contact with the microbes and also some endogenous molecules which are released by tissue damage. As part of the innate immune system, endothelial cells respond to these contacts by producing inflammatory mediators and expressing surface molecules. The initial sensing of microbial and endogenous danger-associated molecules is mediated by so-called pattern recognition receptors (PRRs). PRRs can be classified in different protein families such as the Toll-like receptors, the NODlike receptors and the RIG-I-like receptors. By activating inflammatory gene transcription and posttranslational processing, PRRs control the immediate innate immune reaction and also the subsequent adaptive immune response. Here we describe the current knowledge of extra-and intracellular PRRs in endothelial cells and their potential role in sepsis and vascular diseases.
Keywords: Toll-like receptor; NOD-like receptors; RIG-I-like receptor; endothelial cells